Integrated electrochemical and mass biosensor for early dengue detection - Ahmad Anwar Zainuddin (Kulliyyah of Engineering, International Islamic University Malaysia, 2020)
Dengue illness is an infectious tropical disease, transmitted by Aedes mosquitos which poses a serious health threat to the tropical world. Malaysia is among the seriously affected countries with a rapid increase of 133% of new dengue fever cases and 158% of deaths from 2013 to 2016. Currently, the dengue detection methods such as virus isolation, polymerase chain reaction (PCR), and Enzyme-linked immunosorbent assay (ELISA) are popularly used due to its good sensitivities. However, they require long incubation periods of up to 48 hours with tedious processing steps, thus causing the patients to be diagnosed with dengue when they are at a late stage. To overcome these issues, the usage of biosensors have been proposed as an alternative technology for rapid detection of dengue. The major electrical biosensing strategies, including electrochemical, mass, and optical measurement are widely used because of their high sensitivity and real-time measurements. Among them, optical biosensor has the highest sensitivity, but this method is not applicable as point-of-care (PoC) devices due to its complex and expensive equipment. Alternatively, the use of electrochemical and mass detection method such as electrochemical impedance spectroscopy (EIS) and quartz crystal microbalance (QCM) is highly recommended for detection of dengue due to its simplicity, cost-effectiveness and portability. In this work, an integrated electrochemical quartz crystal microbalance (IEQCM) was successfully developed for early dengue detection (NS1 antigen). This IEQCM sensor has a dual-function working electrode that enables in-situ measurements of both EIS and QCM. When the biological target attaches to the working electrode, the QCM detects shifts in resonance frequency due to dampened acoustic waves propagating through the quartz sensor. The same device can also detect impedance changes due to surface reaction via EIS measurement. The design of the biosensor is first simulated using COMSOL and its design parameters such as radius of working electrodes (rWE) and gap (g) between electrodes are optimized. Experimental measurements were conducted using the fabricated IEQCM to validate these simulation results. The best design parameters of sensors were found to have an array of three, 10MHz IEQCM biosensor on a single substrate with rWE of 2000µm which exhibits highest quality factor (Q-factor = 2.77 x 104). All the QCM sensors operate at a frequency of 9.79 MHz ± 1kHz. For EIS sensor, the optimal g between electrodes was found to be 70µm since it produces the highest current density (based on simulation) to enhance electro-migration of ions at sensor interfaces. The dengue NS1 measurement results, suggested that the EIS measurement showed the higher instrumental sensitivity (12.15 percentage decade-1) than QCM measurements (9.87 percentage decade-1) but the QCM measurement provided higher assay sensitivity in this work. This work has shown that IEQCM has the potential to provide rapid, early and accurate dengue detection in point-of-care settings with higher sensitivity and selectivity.